(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Online education has grown in popularity in recent years. This article examines parents’ attitudes towards the online education system. These new portals have shown to be incredibly beneficial to students from developing and underdeveloped nations. E-learning has significantly altered the approach and procedure for disseminating learning courses and delivering vital knowledge to pupils. Learning online is simple for upper-level students, but it is difficult for primary-level pupils. Against this context, the purpose of this study is to investigate parent satisfaction with the online education system. For the study, the researcher recruited 70 people from the Tirunelveli district. Data was obtained using a structured questionnaire and analysed using statistical tools such as percentage analysis, chi-square analysis, and Garrett ranking analysis.